A study on intention to use social media in higher education: the mediating effect of peer influence. Issue 1 (25th October 2021) - Trivedi, Shrawan Kumar; Patra, Pradipta; Singh, Saumya
Abstract : Purpose: Social media sites are one of the vital technological developments of WEB 2.0. This study aims to emphasize on building an empirical model to investigate the impending determinants of users' intention to use social media sites in higher education. Depending on the existing theories such as the social media acceptance model, e-learning acceptance model, unified theory of acceptance and use of technology and existing literature, determinants such as "performance, " "communication functionality" and "self" have been identified to test. Further, the mediation effect of "peer influence" on the relationship has also been tested. Design/methodology/approach: A total of 310 students of different private and public Indian institutions have participated in an online survey. Exploratory factor analysis and multiple linear regression analysis are performed and results were analyzed. Findings: The results of this study demonstrated substantial evidence of the impact of performance, communication functionality and self on the intention to use social media in higher education. The mediation of peer influence has also been seen between all the relations. Originality/value: An empirical model of intention to use social media in higher education is built. The median of peer influence is tested.